Analisis Perbuatan Melawan Hukum Terkait Kasus Penyerobotan Tanah dalam Putusan Nomor 16/PDT/2022/PT BTN - Andryawan Andryawan; Ririn Khairunisa; Salma Setiawati; Diva Khairunisa; Ellina Dewi; Kezia Estevania Christabel Eliezer (Dinasti Research, 2025)
Land encroachment is a problem that often occurs in social environments, as it falls under the category of unlawful acts, as stated in Article 1365 of the Civil Code, which states that